Parasitism-Mediated Interactions Between the Ring-Legged Earwig and Sugarcane Borer Larvae - Nunes, G. S. [UNESP]; Ramalho, D. G.; dos Santos, N. A.; Truzi, C. C. [UNESP]; Vieira, N. F. [UNESP]; Cardoso, C. P. [UNESP]; De Bortoli, S. A. [UNESP] (Springer Nature, 2019)
Sugarcane is one of the most economically important crops in Brazil. The damage caused by Diatraea saccharalis (F.) (Lepidoptera: Crambidae) results in high costs for its production. Cotesia flavipes Cameron (Hymenoptera: Braconidae) is the most efficient means of controlling this pest. The prohibition of burning and the preservation of soil cover through non-tillage practices increased many population densities of natural enemies of the sugarcane borer (SCB) in sugarcane fields. Euborellia annulipes (Lucas) (Dermaptera: Anisolabididae) is a predator found in sugarcane fields and is associated with predation of SCB. This study aimed to evaluate the influence of parasitism of D. saccharalis by C. flavipes on predation by E. annulipes adult females. For this purpose, fourth instar sugarcane borer larvae were exposed to parasitism over a 5-day period or were not parasitized. Subsequently, the prey was supplied to the predator in arenas under choice and no-choice conditions and under different densities to evaluate the feeding preference over a 12-h period and functional response of the predator over a 24-h period. E. annulipes killed 2–3 fourth instar larvae of the sugarcane borer over a 12-h period. SCB parasitism did not affect the feeding preference of the predator and did not alter the type II functional response. However, the handling time of the predator was lower (1.943 h) and there was a higher T/Th ratio on the non-parasitized larvae (12.352). Our findings indicate E. annulipes as a promising biological control agent of D. saccharalis, with a potential to assist in the sugarcane borer management approaches and could to reduce the costs of parasitoid release in the field.
Keywords: Cotesia flavipes; Diatraea saccharalis; Euborellia annulipes; integrated pest management; trophic interactions